Associations between early emotional and behavioral problems and subsequent mental disorders in children – Findings from a Swedish cohort study - Johanna Dahlen; Anton Dahlberg; Helena Fabian; Natalie Durbeej (PLoS ONE, 2026)
Purpose To explore the associations between early emotional and behavioral problems, measured by the Strengths and Difficulties Questionnaire (SDQ), and subsequent mental disorders among children in a Swedish context. Methods This cohort study used data on emotional and behavioral problems in children aged 3–5 years old (n = 6,646) from the Focus study in Uppsala Region, Sweden. The data included emotional and behavioral problems using the SDQ rated by mothers (n = 6,616), fathers (n = 6,385) and preschool teachers (n = 5,079). The cohort was followed from 2013 to 2022, with psychiatric diagnoses collected from the National Patient Register. Associations between emotional and behavioral problems and later mental disorders were explored using unadjusted and adjusted Cox regression models. Results The proportion of children identified with emotional and behavioral problems, based on the SDQ total difficulties score, was 9.4% according to mothers, 12.2% according to fathers and 7.6% according to teachers. Altogether, 9.2% (n = 611) of the children were diagnosed with a mental disorder during the follow-up period. In unadjusted models, the risk of a mental disorder was significantly higher among children with emotional and behavioral problems, as rated by mothers (HR: 3.59), fathers (HR: 2.67) and teachers (HR: 2.95). This elevated risk remained significant in adjusted models for ratings by mothers (AHR: 3.66), fathers (AHR: 2.66) and teachers (AHR: 3.06). Children with difficulties in the hyperactivity and inattention subscale of the SDQ showed a significantly increased risk of being diagnosed with attention-deficit hyperactivity or conduct disorder when rated by mothers (AHR: 4.19), fathers (AHR: 3.21) and teachers (AHR: 4.88). Conclusion Early emotional and behavioral problems identified using the SDQ are associated with subsequent mental disorders in children in Sweden. These results reinforce the importance of early assessment of children’s emotional and behavioral functioning to enable early identification and intervention for children at risk.